Exposure of Undergraduate Nursing Students to Standing Environments: A Longitudinal Study on Plantar Force and Pressure Distribution - Bernardes, Rafael A. (Lippincott, 2025)
Background: Understanding the link between plantar force, pressure, and foot discomfort is important for nursing students' well-being, given the prevalence of foot and ankle musculoskeletal disorders among nurses. Assessing these factors can inform tailored self-care interventions, supporting holistic nursing education.
Purpose: To assess the plantar force and pressure distribution of third-year nursing students at baseline and after 5 months of exposure to a clinical setting.
Methods: A prospective cohort study in a Portuguese nursing school measured changes in podiatric profile at 5 months, including peak pressure, maximum force, and contact area.
Results: Elevated mean peak pressure in the heel correlated positively with maximum force and contact area. Negative correlations were found between the contact area and edema. Peak pressure correlated positively with thigh pain, indicating pressure transfer to metatarsal heads.
Conclusions: The findings underscore the importance of integrating ergonomic education into nursing curricula and raising awareness of self-care interventions.